Radical climate movements—is the hype about “eco-terrorism” analogy, warning or propaganda? - Lederer, Markus; Lasso Mena, Verena; Marquardt, Jens; Richter, Timo Alexander; Schoppek, Dorothea Elena (Frontiers in Political Science, 2024)
Is the hype about “ecoterrorism” analogy, warning or propaganda? In order to answer this question, we start by defining radicalization, terrorism, and civil disobedience to develop systematic categories which allow us to pursue two specific research goals: First, we analyse how the breadth of the German climate movement is represented in the media, how the issue of “terrorism” is taken up and with what consequences for the debate. Here we make a discursive argument. Secondly, we use the information provided by the media reports, triangulate it with primary data from the movements analysed and secondary data from academic publications in order to assess the validity of the accusation of terrorism. Here we make a factual argument about the current properties of the climate movement. Finally, we bring both arguments together and argue that even the more radical currents of climate activism should not be classified as terrorists. What we can see is that there has been an attempt to criminalize demands of the radical climate movement during which large parts of the German print media have become willing handmaidens in the delegitimization of more or less radical climate groups. More recently, very first signs of a backlash against the criminalization can be detected.